Propriedades da sílica CTA-MCM-41 contendo metacrilatos e seu emprego na transesterificação de monoéster - Araújo, Jailson Arruda de (2013)
The search for clean and renewable fuels has aroused great interest in the industry and scientific community with the growing demand for energy. The transesterification reaction of triglycerides is one way of achieving a sustainable fuel and less harmful to the environment. This has encouraged researchers to develop new routes of synthesis of heterogeneous catalysts. The CTA-MCM-41 silica has basic catalytic sites called siloxy (≡SiO-) and may be used in transesterification reactions. Its use in base catalysis has shown promising results, but the reuse reveals extensive loss of activity due to the removal of CTA cations from the channels. The catalyst modification may improve the catalytic stability, in which the insertion of polymeric species together the micelles within the silica is one method studied by our group. Given this perspective, this study aimed at evaluating the modification of the basic catalyst CTA-MCM-41. The polymers encapsulation and ultraviolet irradiation on silicas containing monomer were performed in this study. It was possible to prove by means of small angle X-ray scattering conducted on the emulsion and silicas, the polymeric and monomeric species were inside the micelles causing micellar and silica expansion. The infrared absorption spectroscopy, X-ray diffraction and chemical analysis showed that these species remained inside the micelles after encapsulation. The catalytic evaluation demonstrated that the modified silica with low amounts of monomer added showed improved catalytic stability.